PENINGKATAN KETERAMPILAN KADER POSYANDU DALAM MEMBERIKAN EDUKASI DENGAN METODE EMOTIONAL DEMONSTRATION DALAM UPAYA PENCEGAHAN STUNTING DI POSYANDU CEMPAKA DESA PONDOK MEJA KECAMATAN MESTONG MUARO JAMBI - M. Ridwan; Hendra Dhermawan Sitanggang; Helmi Suryani Nasution (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2023)
Stunting is still a public health problem in Pondok Meja Village, one of which is in the Cempaka posyandu area. The results of an interview with the Head of the Cempaka Posyandu Cadre, Pondok Meja Village, stated that in the Cempaka Posyandu, Pondok Meja Village, Muaro Jambi itself recorded ten children who were stunted and were currently under the supervision of the Pondok Meja village government and received assistance from the village. For this reason, the ability of cadres must be improved, one of which is the Emotional Demonstration (Emo Demo) method. The emotional demonstration approach is one way of health education through interactive education sessions using games between individuals, groups or communities involving child development stages. Based on this, the ability of cadres to provide counselling must continue to be improved, especially with the proper method, so that it can facilitate its implementation. This method is designed with a demonstration approach that plays on emotional aspects. With this method, the community will more easily understand the problems that cause stunting.